Brd/BET Proteins Influence the Genome-Wide Localization of the Kaposi’s Sarcoma-Associated Herpesvirus and Murine Gammaherpesvirus Major Latency Proteins - Lotke, Rishikesh; Schneeweiß, Ulrike; Pietrek, Marcel; Günther, Thomas; Grundhoff, Adam; Weidner-Glunde, Magdalena; Schulz, Thomas F. (Frontiers in Microbiology, 2020)
The rhadinoviruses Kaposi’s Sarcoma-associated herpesvirus (KSHV) and murine gammaherpesvirus (MHV-68) persist in infected hosts in a latent state that is characterized by the absence of virus production and by restricted viral gene expression. Their major latency protein, the latency-associated nuclear antigen (kLANA for KSHV and mLANA for MHV-68), is essential for viral genome maintenance and replication and involved in transcriptional regulation. Both kLANA and mLANA interact with cellular chromatin-associated proteins, among them the Bromodomain and Extra Terminal domain (Brd/BET) proteins, which recruit cellular and viral proteins to acetylated histones through their bromodomains and modulate cellular gene expression. Brd/BET proteins also play a role in the tethering, replication, segregation or integration of a diverse group of viral DNA genomes. In this study we explored if Brd/BET proteins influence the localisation of the LANAs to preferential regions in the host chromatin and thereby contribute to kLANA- or mLANA-mediated transcriptional regulation. Using ChIP-Seq, we revealed a genome-wide co-enrichment of kLANA with Brd2/4 near cellular and viral transcriptional start sites (TSS). Treatment with I-BET151, an inhibitor of Brd/BET, displaced kLANA and Brd2/4 from TSS in the viral and host chromatin, but did not affect the direct binding of kLANA to kLANA-binding sites (LBS) in the KSHV latent origin of replication. Similarly, mLANA, but not a mLANA mutant deficient for binding to Brd2/4, also associated with cellular TSS. We compared the transcriptome of KSHV-infected with uninfected and kLANA-expressing human B cell lines, as well as a murine B cell line expressing mLANA or a Brd2/4-binding deficient mLANA mutant. We found that only a minority of cellular genes, whose TSS are occupied by kLANA or mLANA, is transcriptionally regulated by these latency proteins. Our findings extend previous reports on a preferential deposition of kLANA on cellular TSS and show that this characteristic chromatin association pattern is at least partially determined by the interaction of these viral latency proteins with members of the Brd/BET family of chromatin modulators.